The Relationship of Anticipatory Gluteus Medius Activity to Pelvic and Knee Stability in the Transition to Single‐Leg Stance. Issue 2 (14th June 2015) - Kim, Daehan; Unger, Janelle; Lanovaz, Joel L.; Oates, Alison R.
Abstract: Background: The knee abduction moment in a weight‐bearing limb is an important risk factor of conditions such as patellofemoral pain and knee osteoarthritis. Excessive pelvic drop in single‐leg stance can increase the knee abduction moment. The gluteus medius muscle is crucial to prevent pelvic drop and must be activated in anticipation of the transition from double‐leg to single‐leg stance. Objective: To examine the relationship of anticipatory activity of the gluteus medius to pelvic drop and knee abduction moment. Design: Observational, cross‐sectional correlational study. Setting: Research laboratory. Participants: Twenty female adults (mean age 22.6 years, standard deviation 2.5) were recruited and fully participated. Participant selection was limited to healthy women who did not have a history of knee and ankle ligament injuries, any indication of knee, hip, and/or low back pain, and/or knowledge of the proper squat technique. Methods: Participants performed 16 single‐leg mini squats on their nondominant leg. Main Outcome Measures: The onset and magnitude of anticipatory gluteus medius activity were measured in relation to toe‐off of the dominant leg during the transition from double‐leg to single‐leg stance. Preplanned correlations between anticipatory gluteus medius onset and its activation magnitude, pelvic obliquity, and knee abduction moment were examined. Results: The magnitude of anticipatory gluteus medius activity was significantly correlated with the knee abduction moment (rs (18) = −0.303, P < .001) and pelvic obliquity (rs (18) = 0.361, P < .001), whereas gluteus medius onset was not significantly correlated with either knee abduction moment or pelvic obliquity. Conclusions: The amount of gluteus medius activity is more important for controlling knee and pelvic stability in the frontal plane than the onset of activation.